Service evaluation under rules tested at Volleyball Men’s Under 23 World Championship (Evaluación del saque en función de las reglas probadas en el Campeonato del Mundo de Voleibol Masculino sub-23) - Mladen Stankovic; Guillermo Ruiz-Llamas; Dušan Perić; Miriam E. Quiroga-Escudero (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In a sample of 36 matches from the inaugural Volleyball Men’s Under 23 World Championship played using two experimental rules (set to 21 points, excluding the fifth set; 15 seconds between points), 4588 serves were analysed. Analysing 123 sets, the aim of the study was to determine the influence of the new rules on the serve in relation to in-game role, serve type, serve quality, serve trend by set phase, serve zone and placement zone. Pearson’s Chi-Square test was used for data analysis. Significant differences were observed in serve type by set phase (p = .000), serve quality of set Winner and set Loser teams (p = .000), serve zone by set Winner and set Loser teams (p = .000), placement zone by serve zone (p = .004), serve quality distribution by serve zone (p = .039), serve quality distribution by placement zone (p = .000), serve type distribution by in-game role (p = .000), serve quality distribution by in-game role (p = .000), and serve zone distribution by in-game role (p = .000). This study can help volleyball coaches organise their training programmes and match strategies and set appropriate physical preparation for serve requirements. It also provides insight for Fédération Internationale de Volleyball (FIVB) on the influence of the tested rules for further developments in this sport.